2013
DOI: 10.4300/jgme-d-12-00316.1
|View full text |Cite
|
Sign up to set email alerts
|

Getting Out of Silos: An Innovative Transitional Care Curriculum for Internal Medicine Residents Through Experiential Interdisciplinary Learning

Abstract: Background Care transitions are common and highly vulnerable times during illness. Physicians need better training to improve care transitions. Existing transitional care curricula infrequently involve settings outside of the hospital or other health care disciplines. Intervention We created a curriculum to teach internal medicine residents how to provide better transitional care at hospital discharge through experiential, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Published reports of educational interventions have included postdischarge visits for patients that residents had treated in the hospital and postdischarge and sites of care visits occurring during the 2-to 4-week geriatric or transitions of care rotations. [17][18][19] Embedding the curriculum in the ambulatory schedule facilitated teaching larger groups of interns, and the block scheduling helped with scheduling home care nurses and SNF providers. Our approach did not allow interns to see patients for whom they had provided care in the hospital, but we demonstrated both the feasibility of the visits and the interns' self-reported learning of key transition issues, likely due to the strength of experiential learning with patients and health care teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published reports of educational interventions have included postdischarge visits for patients that residents had treated in the hospital and postdischarge and sites of care visits occurring during the 2-to 4-week geriatric or transitions of care rotations. [17][18][19] Embedding the curriculum in the ambulatory schedule facilitated teaching larger groups of interns, and the block scheduling helped with scheduling home care nurses and SNF providers. Our approach did not allow interns to see patients for whom they had provided care in the hospital, but we demonstrated both the feasibility of the visits and the interns' self-reported learning of key transition issues, likely due to the strength of experiential learning with patients and health care teams.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Residents are responsible for care transitions, yet feel they lack the knowledge of how to safely complete these tasks, and studies have found a need to increase resident knowledge in transitions of care. [12][13][14][15][16][17][18][19] Experiential learning theory suggests that learning is best done in the context in which it occurs, and that interactions are fundamental to gain understanding. 20,21 To address the need for experiential learning, we embedded an innovative curriculum in our existing postgraduate year 1 (PGY-1) ambulatory block.…”
Section: Introductionmentioning
confidence: 99%
“…Le taux d'occupation est encore insuffisant et des efforts sont désormais entrepris pour que l'hôpital adresse plus de patients lorsqu'un séjour en structure intermédiaire paraît indiqué et pour inviter les médecins de la région à suivre leurs patients dans cette structure. L'opportunité de développer une seconde structure intermédiaire dans le canton pour garder cette proximité des soins est à l'étude, tout en portant une attention particulière au curriculum des médecins responsables pour s'assurer qu'ils mettent l'accent sur la liaison avec les autres services ambulatoires [27].…”
Section: Discussionunclassified
“…For example, social workers, pharmacists, occupational therapists and physiotherapists in GIM units have experienced changes in their roles in the healthcare division of labour with greater emphasis on discharge-related responsibilities (Galati, Wong, Morra, & Wu, 2011;Goldman et al, 2016;Neeman et al, 2017). Physicians in these settings have pressures to prioritize their decision-making around patient flow with an increasing emphasis on the value of teaching residents about safe discharge (Greysen, Schiliro, Horwitz, Curry, & Bradley, 2012;Schoenborn & Christmas, 2013). New discharge professional roles have been created to facilitate admissions and discharge in acute care medical units (Okoniewska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%